Ipsilateral Lymphatic and Venous Malformations Affecting the Midface Area - Şükran Bekdemir; Ahmet Kaan Gündüz; Ömür Ataoğlu (Case Reports in Ophthalmological Medicine)
A 22-year-old woman presented with progressive swelling of the nasal conjunctiva in the left eye. Anterior segment examination revealed a diffuse cystic appearance to the inferonasal bulbar conjunctiva and plica semilunaris. Anterior segment swept-source optical coherence tomography (OCT) revealed clear hyporeflective spaces demarcated by hyperreflective septae in the affected conjunctiva, consistent with the diagnosis of lymphatic malformation (LM). Magnetic resonance imaging revealed a well circumscribed intraconal mass located inferonasally in the left orbit. Systemic examination revealed a lesion similar to LM on the left hard palate. The left conjunctival mass was excised subtotally. Subsequently, a transconjunctival anterior orbitotomy was performed and the left orbital mass was completely removed intact. Histopathologically, the conjunctival mass was diagnosed as LM and the orbital mass as venous malformation (VM). This case represents a rare coexistence of histopathologically proven conjunctival LM and orbital VM as well as a presumed LM of the hard palate, all 3 lesions occurring in the ipsilateral midface area.